2018
DOI: 10.1080/09638288.2018.1513086
|View full text |Cite
|
Sign up to set email alerts
|

A goal management intervention for patients with polyarthritis and elevated levels of depressive symptoms: a quasiexperimental study

Abstract: Purpose: Goal was to establish whether an intervention that aims to increase goal management competencies is effective in decreasing elevated levels of depressive symptoms and increasing well-being in patients with polyarthritis. Materials and methods: Eighty-five persons with polyarthritis and elevated levels of depressive symptoms participated in the goal management intervention consisting of six group-based meetings. A quasiexperimental design with baseline measurement, follow-up at 6 months and a reference… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(8 citation statements)
references
References 61 publications
(91 reference statements)
0
8
0
Order By: Relevance
“…The first was a protocol for randomized controlled trial of a psycho-educational programme (Right on Target) (Arends et al, 2013). The second evaluated the Right on Target intervention using a quasi-experimental design (Arends et al, 2018), and the third evaluated a psychological intervention (Self-system therapy) using a randomized controlled trial design (Eddington et al, 2015). The aims of the remaining quantitative studies (n = 7; 13%) were varied.…”
Section: Mapping Of Goal Adjustment Literaturementioning
confidence: 99%
See 3 more Smart Citations
“…The first was a protocol for randomized controlled trial of a psycho-educational programme (Right on Target) (Arends et al, 2013). The second evaluated the Right on Target intervention using a quasi-experimental design (Arends et al, 2018), and the third evaluated a psychological intervention (Self-system therapy) using a randomized controlled trial design (Eddington et al, 2015). The aims of the remaining quantitative studies (n = 7; 13%) were varied.…”
Section: Mapping Of Goal Adjustment Literaturementioning
confidence: 99%
“…Neutral Associations: Seven studies reported neutral associations between goal disengagement and health and/or wellbeing variables. Four were in people with cancer (Mens & Scheier, 2016;Schroevers et al, 2008;Thompson et al, 2013;Zhu et al, 2015); one in people with myocardial infarction (Garnefski et al, 2009b), one in people with arthritis (Arends et al, 2018) and one in people with vasculitis (Mayor, 2018). Three studies reported neutral associations between goal reengagement and recovery and /or wellbeing variables; one in people with cancer (Zhu et al, 2015), one in people with arthritis (Arends et al, 2018) and the final one in people with vasculitis (Mayor, 2018).…”
Section: Synthesis Of the Goal Adjustment Literaturementioning
confidence: 99%
See 2 more Smart Citations
“…With increasing age, individuals show higher investment in strategies of accommodative coping (Brandtstädter & Greve, 1994; Brandtstädter, Rothermund, Kranz, & Kühn, 2010; Rothermund & Brandstädter, 2003). Moreover, accommodative goal management strategies in later life have been found to be associated with better physical and functional health (Arends, Bode, Taal, & Van de Laar, 2018; Hall et al, 2010; Kelly, Wood, & Mansell, 2013).…”
Section: Accommodative Coping and Information-processing Speed As Res...mentioning
confidence: 99%